Effects of Sodium Benzoate Application, Silage Relocation, and Storage Time on the Preservation Quality of Sugarcane Silage - Melany S. Souza; Amanda C. M. de Queiroz; Thiago F. Bernardes; Cristian Faturi; Felipe N. Domingues; João P. P. Rodrigues; Thiago C. da Silva; Aníbal C. do Rêgo (Agronomy, 2022)
The present study explored the effects of sodium benzoate (SB), relocation, and storage time on the quality of sugarcane silage. The experiments followed a completely randomized design with a 2 × 4 × 2 factorial arrangement and four replicates. The treatments were as follows: (i) with (SB+) or without (SB−) SB (2 g∙kg−1 on a fresh matter basis); (ii) with (R) or without (R0) relocation for 12, 48, and 72 h (R12, R48, and R72, respectively); and (iii) storage for 10 or 60 days after relocation. SB− silage showed a lower (p < 0.05) dry matter loss (DML = 155 g·kg−1) without relocation (R0). SB+ silage showed the highest (p < 0.05) DML (257 g·kg−1) with R72. SB use reduced (p < 0.05) the yeast count in silage that was stored for 10 days (SB+: 4.63 CFU·g−1; SB−: 5.58 CFU·g−1). The yeast count was higher (p < 0.05) in silage that was stored for 10 days after relocation, regardless of the relocation time. SB use increased the aerobic stability of silage after 10 days of storage. Thus, SB application is effective for the inhibition of yeast in relocated sugarcane silage. We recommend the use of SB when silage is relocated for 12 h and stored for 60 days after relocation.